Dari Wahyu ke Inovasi: Integrasi Ayat Qauliyah dan Ayat Kauniyah dalam Membangun Peradaban IPTEK - Anggun Risfiani; Aulya Al Azahra; Alihan Satra (Advances In Education Journal, 2026)
The qauliyah verses are revelations from Allah SWT contained in the Qur'an, while the kauniyah verses are signs of Allah's greatness found in the universe. This study aims to determine the relationship between the qauliyah verses and the kauniyah verses in the development of science and technology and the importance of integrating the two in modern life. The method used is qualitative research with a library research approach through data collection from books, journals, scientific articles, and other relevant sources. The results of the study indicate that the integration of the qauliyah verses and the kauniyah verses is important in the development of science and technology so that science is not only oriented towards material progress, but also based on spiritual, moral, and ethical values. The application of this integration can be found in the fields of education, health, environment, technology, and social life. Therefore, the integration of the two is necessary to realize the development of science and technology that is beneficial, balanced, and responsible for human life.